Swimming coaches competences in the opinion of expert coaches - Seweryniak, Tomasz; Muracka, Justyna; Stosik, Aneta (Quality in Sport, 2016)
Competence athletic trainers are of great importance to the quality of education in the system of Polish sport. Unfortunately publications on the competence of the trainers take this issue unilaterally, without taking into account the full specifics of their work. Prepared article seeks to increase knowledge about the competence of the trainers working with high-class swimmers. The study was based on interviews with coaches with high seniority and the results to be considered surveyed by experts. Respondents’ opinions compared with the literature to determine the set of competencies specific to the high-class coaches swimmers.